Evaluation of Paint Industry Effluents for Irrigation Purposes (Biological Sciences - PJSIR, 2006)
Effluent samples collected from a paints factory for a period of seven months were analyzed for pH, electrical conductivity (EC), soluble cations and anions, nitrogen, phosphorus, and trace elements (Cd, B, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Pb). Compared with the natural groundwater used for washing paint wastes, the paint industry effluents were found to contain elevated concentrations of cations with the exception of Ca and moderately high concentrations of trace elements. Evaluation of the effluents was made, based on the integration of EC and both the sodium absorption ratio (SAR) and soluble sodium percent (SSP), BOD and COD values, and maximum permissible limits of heavy metals in the irrigation water. From the overall assessment, the effluents were considered suitable for use as supplement irrigation water. However, it is essential that the heavy metals in the effluents, as well as their accumulation in plants and soils, are monitored regularly.